2014
DOI: 10.1161/strokeaha.114.006076
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Hemispheric Infarction

Abstract: A previously healthy, right-handed 43-year-old man was found lying on the floor in his apartment. His relatives had been unable to contact him for more than a day. On admission, he was somnolent but attempted to obey commands and had a right-sided hemiplegia, dense sensory loss, severe word-finding difficulty, and anisocoria with miosis and ptosis in left eye (National Institutes of Health Stroke Scale, 21). Emergent computerized tomographic scan revealed an extensive left-hemispheric infarction (Figure [A]). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Decompressive craniectomy (DC) has been shown to be effective in lowering mortality in patients with malignant MCA infarction. DC is aimed to remove part of the ipsilateral cranium to allow outward herniation of the infarcted brain tissue before compression of formerly healthy brain tissue occurs, decrease the ICP and improve cerebral perfusion pressure, thereby aiding the blood flow to the ischemic penumbra 10 11 12 . Recently, three randomized controlled trials (RCTs) and their pooled analyses suggested that early DC significantly reduced mortality and improved favorable outcome defined as modified Rankin scale (mRS) ≤ 4 13 14 15 16 .…”
mentioning
confidence: 99%
“…Decompressive craniectomy (DC) has been shown to be effective in lowering mortality in patients with malignant MCA infarction. DC is aimed to remove part of the ipsilateral cranium to allow outward herniation of the infarcted brain tissue before compression of formerly healthy brain tissue occurs, decrease the ICP and improve cerebral perfusion pressure, thereby aiding the blood flow to the ischemic penumbra 10 11 12 . Recently, three randomized controlled trials (RCTs) and their pooled analyses suggested that early DC significantly reduced mortality and improved favorable outcome defined as modified Rankin scale (mRS) ≤ 4 13 14 15 16 .…”
mentioning
confidence: 99%